Personalidade e bem-estar subjetivo: o papel mediador do fenômeno do impostor em crianças - RAFAELA TEODORO ALVES (2024)
The aim of this dissertation was to evaluate the relationship between personality traits, subjective well-being, and the imposter phenomenon in children. To achieve this goal, two manuscripts were developed. The first had a qualitative approach and sought to gather information on the connection between impostorism and mental health variables through a systematic review. Fifty-four relevant articles were analyzed, included after the application of readability criteria. The results highlighted several mental health variables related to the IP and demonstrated that impostorism manifests in various contexts and samples, in addition to the need for more research in this field. The second manuscript, of an empirical nature, aimed to assess to what extent personality traits, subjective well-being, and the imposter phenomenon are related in a sample of children. One hundred seventeen elementary school students from Campo Grande (MS), with an average age of 11 years, participated in the study. The results revealed a significant negative correlation between the imposter phenomenon and overall wellbeing, as well as it being predicted by the IP and by extraversion, openness to change, and conscientiousness. These findings indicate the importance of subjective well-being and personality traits in understanding impostorism, highlighting the need for future research to expand on these results. In summary, the results obtained in the two manuscripts contribute to achieving the overall objective of this dissertation.